Ecological Education in ELT; How Could It Promote Students’ Critical Thinking Skill and Sustainable Behaviour? - Maghfiroh, Ana; Harmanto, Bambang; Prayitno, Harun Joko; Tamrin, Agusti; Lathifah, Lathifah (Universitas Pendidikan Mandalika, 2025)
Education has been recognised as a fundamental part of local, national and international efforts to bring about environmental sustainability. However, some schools are confused to integrate it in school program and to raise students awareness towards the environmental issues. The purpose of this study is to explore the integration of ecological education (Eco-Edu) in English Language Teaching (ELT) materials and its role in promoting students’ critical thinking and sustainable behaviour. This research employed a descriptive qualitative method. For triangulation data, the researchers combined qualitative data from interviews and quantitative data from questionnaires. The respondents of this study were teachers from five different schools which have integrated the ecological theme in ELT materials. Five informants from five schools were interviewed extensively to collect qualitative data. The interviews were analyzed through thematic analysis using ChatGPT application tools. The findings of this study indicated that teachers were able to integrate the environmental education by applying various ecological themes in ELT materials which could promote the students’ critical thinking and raise their sustainable behavior. Teachers noted that students became more proactive in environmental initiatives, such as waste management and tree planting, reflecting a greater awareness of ecological concerns. Moreover, the study highlighted the importance of institutional support and teacher preparedness in successfully implementing Eco-Edu. Ultimately, the integration of Eco-Edu in ELT not only improved language skills but also cultivated a sense of responsibility toward the environment, equipping students with the knowledge and motivation to address global ecological challenges.